Trend of Students Religiosity Viewed Gender and Background Majors - Eliasa, Eva Imania; Ilfiandra, Ilfiandra; Yusuf, Syamsu (Universitas Muhammadiyah Metro, 2018)
This study aims to determine the trend of student religiosity in terms of gender and background majors. The research approach uses a quantitative approach to the type of cross-sectional survey. Participants numbered 292 (58 male and 234 female) students in the Faculty of Education taken with non-probability random sampling technique. The data collection technique used a scale. The research instrument used Religiosity Scale for Youth from Hernandez. The test of validity, using the Pearson product-moment correlation, with 37 items that valid and reliability using Cronbach Alpha test with 0893. Data were analyzed using quantitative descriptive technique and Two Way Anova. The results showed that the trend of religiosity students Including a high category in the aspect of religious belief, and the category is quite high in the aspect of religious activity. The overall dynamics of the diversity of students in the category is quite high, and the majors PLB, PLS, PGSD has a higher category. There is no difference between the gender with religiosity, but female students are higher than males.